Maksimalisasi Keuntungan pada Bisnis “Naya Online Shopping” dengan Metode Simpleks - Diva Nadhofah Sadarisma; A. Rama El Shinta; Zulfa Nabila Kulsum; Dedek Kustiawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Linear programming is one of the most widely used operations research techniques in practice and is known for being easy to understand. The method for completing the linear program in the "Naya Online Shopping" method is the graphical method simplex. The purpose of completing this linear program is to optimize the amount of production in obtaining maximum profit. And the optimal solution is obtained, namely the maximum profit of IDR 1,750,000, with the number of ting-ting bags to be purchased from agents as many as 50 and the number of crown wallets to be purchased from agents as many as 100. From a maximum storage capacity of 150 pieces, it can be maximized by purchasing 50 bags and purchasing 100 wallets. Completion of the linear program with the graphical method of operations research and the simplex method get the same result.